The Effect of Eddy-bubble Interaction Model on the Turbulent Dispersion of Gas Bubbles in Stirred Tanks - 韩路长 曹杨 吴学文 白鸽 刘跃进 (Chinese journal of chemical engineering, 2010)
Based on trajectory equations of gas bubble,an eddy-bubble interaction（EBI）model was developed. This model considered the effect of non-drag forces and took the eddy-bubble interaction time as the refreshing time scale of turbulent fluctuations.The relationship between the crossing-eddy time and the eddy lifetime was discussed,and the predicted distributions of radial,axial velocities of bubbles and gas holdup were also given. Compared with eddy lifetime（EL）model,the EBI model gives somewhat smaller axial velocity in the upper circulation region and larger velocity in the lower circulation region,causing that fewer bubbles reach the lower circulation region and gas holdup becomes higher in the upper circulation region.The predicted gas holdup by the EBI model approaches closer to the experimental data in the discharge stream region.